2008
DOI: 10.1021/ic702201e
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Gold(I) Carbenes from 2-Pyridylisocyanide Complexes: Structural Consequences of Intramolecular versus Intermolecular Hydrogen-Bonding Interactions

Abstract: Isocyanide [AuX(CNPy-2)] (X = Cl, C6F5, fluoromesityl, 1/2 octafluorobiphenyl) and carbene [AuX{C(NR1R2)(NHPy-2)}] (R1R2NH = primary or secondary amines or 1/2 primary diamine) gold(I) complexes have been synthesized and characterized. For X = Cl, the carbene complexes show aurophilic interactions. The fragment NHPy-2, formed in the carbenes, can give rise to intra- (for primary amines) or intermolecular (for secondary amines) hydrogen bonds, depending on the amine used. These bonds and contacts have been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
42
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 47 publications
13
42
1
Order By: Relevance
“…Two years later the same authors also reported the synthesis of the first five nitrogen acyclic carbene (NAC, Figure 2) complexes of gold by addition of primary amines to isonitrilegold chloro complexes. [11] Applications of the isonitrile and NAC gold complexes in the field of luminiscent compounds, [12] laser-induced writing with gold on ceramic surfaces, [13] liquid crystals [14] and water-soluble complexes [14] have been reported. The first NHC complex of gold(I) was prepared in 1989, [15] and at present these gold carbene complexes are the dominating car- …”
Section: Introductionmentioning
confidence: 99%
“…Two years later the same authors also reported the synthesis of the first five nitrogen acyclic carbene (NAC, Figure 2) complexes of gold by addition of primary amines to isonitrilegold chloro complexes. [11] Applications of the isonitrile and NAC gold complexes in the field of luminiscent compounds, [12] laser-induced writing with gold on ceramic surfaces, [13] liquid crystals [14] and water-soluble complexes [14] have been reported. The first NHC complex of gold(I) was prepared in 1989, [15] and at present these gold carbene complexes are the dominating car- …”
Section: Introductionmentioning
confidence: 99%
“…5 We have recently reported that gold(I) complexes with other types of carbene ligands, that we have named HBHCs (hydrogen bonded heterocyclic carbenes, e.g., [AuCl{C(NRH)(NHPy-2)}]), or NAC (nitrogen acyclic carbenes, e.g., [AuCl{C(NHR)(NHR 0 )}] or [AuCl{C(NHR)(NR 0 2 )}]), are good catalysts in skeletal rearrangement and in methoxycyclization of enynes, [6][7][8] suggesting that this kind of carbene complexes should be incorporated Article Inorganic Chemistry, Vol. 49, No.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, most of the complexes described here display luminescent properties [28] . In a related study conducted by Espinet et al [29] , the isocyanide in complexes [AuX(CNPy -2)] (X = Cl, C 6 F 5 , F mes ) were shown to react with H 2 NMe or HNEt 2 to produce the aminocarbene species [AuX{C(NR 1 R 2 )(NHPy -2)}]. The NHPy -2 moiety generated in this reaction gives rise to either intramolecular (for primary amines) or intermolecular (for secondary amines) hydrogen bonds.…”
Section: Introductionmentioning
confidence: 90%
“…The NHPy -2 moiety generated in this reaction gives rise to either intramolecular (for primary amines) or intermolecular (for secondary amines) hydrogen bonds. Except for the fl uoromesityl derivatives, the carbene complexes display luminescent properties [29] .…”
Section: Introductionmentioning
confidence: 99%